2015
DOI: 10.1007/s00167-015-3611-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity rotational deformities and patellofemoral alignment parameters in patients with anterior knee pain

Abstract: Diagnostic study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 49 publications
(94 reference statements)
4
68
0
2
Order By: Relevance
“…In contrast to adults, for whom PFP is often assumed to be a kinematic problem, overuse is most often cited as the etiology of pain for adolescent patients. 28, 44, 46, 47, 52 There are a plethora of analyses 6, 9, 12, 24, 37, 50 on patellar tracking and alignment patterns in adults with PFP. Yet, an extensive search of the literature revealed no studies on patellar tracking and just two studies 17, 33 on patellar alignment in adolescents with PFP.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to adults, for whom PFP is often assumed to be a kinematic problem, overuse is most often cited as the etiology of pain for adolescent patients. 28, 44, 46, 47, 52 There are a plethora of analyses 6, 9, 12, 24, 37, 50 on patellar tracking and alignment patterns in adults with PFP. Yet, an extensive search of the literature revealed no studies on patellar tracking and just two studies 17, 33 on patellar alignment in adolescents with PFP.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was found a 1.56-fold higher mean femoral anteversion in patients with a history of patellofemoral instability compared with controls. But no signi cant differences in tibial torsion were found in patients with patellofemoral instability compared to the control group in the above two studies [3,4].…”
Section: Introductionmentioning
confidence: 80%
“…Так, многими исследованиями доказа-но, что наружная ротация большеберцо-вой кости в значимой степени увеличивает стресс-нагрузку на фасетки надколенника, приводит к ранней нестабильности пателло-феморального сустава и компрессионному болевому синдрому [38,39]. В частности, Lee и соавт.…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified